Attracting Tourists Back: The Effect of Destination Attributes on Revisit Intentions - Sella Sades (Program Studi Manajemen Institut Manajemen Koperasi Indonesia Bandung, 2024)
This study examines the factors influencing tourists' revisit intentions to a destination, focusing on physical attributes, variety of activities, service quality, and price perception. Utilizing an online questionnaire, data were collected from tourists, and the analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results reveal that all four factors have a significant impact on revisit intentions. First, physical attributes, including the quality of infrastructure and environmental aesthetics, significantly influence tourists' decisions to return to a destination. Second, the variety of activities available at a destination is crucial in enhancing the tourist experience, catering to diverse preferences, and boosting the likelihood of repeat visits. Third, service quality, particularly in terms of responsiveness, reliability, and empathy, has the strongest influence on revisit intention, indicating that high levels of service excellence are critical for fostering loyalty among tourists. Lastly, price perception, which reflects the tourists’ views on the fairness and value-for-money of the offerings, also plays a significant role in shaping revisit intentions. These findings suggest that destination managers should focus on enhancing physical attributes, diversifying activities, ensuring high service quality, and adopting competitive pricing strategies to improve tourist satisfaction and increase the likelihood of repeat visits. The study contributes to the body of knowledge on tourism management by providing insights into the key drivers of tourist loyalty and offering practical implications for destination marketing strategies. Future research could explore other variables, such as cultural and social factors, that may further influence revisit intentions.